KARAKTERISTIK PENGGUNA DAN APLIKASI PADA TINGKAT PENGGUNAAN (STICKINESS) APLIKASI VIDEO PENDEK XYZ - Gagan Gandara; Ujang Sumarwan; Sufrin Hannan (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This study aimed to analyze differences in user characteristics (demographics and motivation) and the XYZ application characteristics (content category and service quality) at the level of use (stickiness). This study's respondents were 797 daily users, consisting of 584 uploaders (have uploaded videos) and 213 watchers (never uploaded videos. The data processing methods used were descriptive analysis and Kruskal Wallis and Mann Whitney U difference test. The results showed that the users were mostly male, aged 18-30 years, had a high school education level and income below 2 million rupiahs per month. The motivations for sharing videos were mostly to make money, share with friends and family, and gain followers. The most preferred content categories by watchers were good looking women, comedy, and scenery. Watchers were satisfied with the existing content category. Uploaders had a neutral preference for service quality. Accumulatively, 90.8% of all respondents used the application for 10-30 minutes or more daily. The motivation to share videos, the most preferred content category, the quality of service, namely the ease of recording videos, and the completeness and suitability of the music catalog were significantly different at the level of use. Managerial implications are addressed in terms of content development, enhancement of all aspects of service quality, and promotion strategies to improve XYZ application performance. Keywords: content category, demographics, motivation, service quality, stickiness